The effectiveness of online media in reducing the plaque rate of elementary school children: A systematic literature review - Ana Riolina (Science Midwifery, 2026)
The high prevalence of dental plaque in elementary school children is still a dental and oral health problem that can affect children's quality of life. The development of information technology encourages the use of online media as an alternative to dental and oral health education. This study aims to analyze the effectiveness of online media in reducing plaque rates in elementary school children through a bibliometric approach and literature review. Article searches were conducted through the Scopus database and the Web of Science in the 2020–2025 publications. The initial search results obtained 307 articles, then after the process of checking duplication, screening, and selection based on inclusion and exclusion criteria, 20 articles were obtained that were eligible for review. Data analysis was carried out using VOSviewer, Biblioshiny, and Rayyan.ai. The results of the study show that online media such as mobile applications, educational videos, gamification, chatbots, and web-based platforms are effective in improving dental and oral health knowledge, tooth brushing behavior, and plaque control in children. In addition, parental involvement through digital media also supports the improvement of children's oral hygiene. In conclusion, online media has the potential as a promotive and preventive media in reducing the number of plaques in elementary school children.